Dynamics of the indicators of physical development, physical and technical fitness of young 12 - 15 year old weightlifters of the different groups of weight categories - Lutovinov Iu.A; Oleshko V.G; Lisenko V.N; Tkachenko K.V (Kharkov National Pedagogical University, 2012)
Here is the dynamics of indicators of physical development, physical and technical preparedness of young 12 - 15 year old weightlifters who are training for the Championship of Ukraine. 50 sportsman's has taken part in investigation. Age of sportsman - 12 - 15 years old. The indicators of physical development and preparedness of sportsmen were researched. The indicators of physical preparedness in control snatch, clean and jerk exercises were analyzed. The interconnection among the indicators of physical development as well as general and special physical preparedness of young weightlifters was shown. It was analyzed that the body length indicators of sportsmen are tend to grow by 15.2 % with an increase of weight category groups. It was estimated that the index of active mass of sportsman body grows by 14.2% with an increase of weight category groups. It was analyzed that the length indicators of upper and low extremities of young weightlifters grow on average by 14.6% and 15.1% with an increase of weight category groups. It was estimated that the indicators of general and special physical preparedness of young weightlifters grow on average by 18.2% and 40.8%.